Real-time observation of stress-induced domain evolution in a [011] PIN-PMN-PT relaxor ferroelectric single crystal. (15th August 2019) - Liu, Ying; Xia, Junhai; Finkel, Peter; Moss, Scott D.; Liao, Xiaozhou; Cairney, Julie M.
Abstract: This paper reports on the real-time observation of mechanical stress-induced micro and nano domain evolution in a single crystal relaxor ferroelectric [011] poled 24PIN-PMN-PT "3-2 mode" nano-sized lamella. Mechanical loading in the [100] direction was applied to lamella in situ within a transmission electron microscope, with a [ 0 1 ¯ 1 ] viewing direction selected for the recording of real-time videos of the domain evolution within the lamella. The observed dominant behaviour under loading is a reversible response composed of the movement of microdomains and the disappearance of nanodomains. Changes in the selected area diffraction pattern down the [ 0 1 ¯ 1 ] zone axis are reported, and provide evidence of a significant increase in crystal symmetry under compression. A qualitative insight into the behaviour of the lamella's mechanical response is obtained via predictions of the non-uniform stress distribution within the lamella found using simple finite element analysis. The correlation between the observed morphology changes, diffraction pattern changes, and the known mechanical stress induced polydomain-rhombohedral to monodomain-orthorhombic phase transition of bulk [011] poled 24PIN-PMN-PT "3-2 mode" single crystal is discussed. Graphical abstract: Image 1